الحداثة وما بعد الحداثة من منظور عبد الوهاب المسيري - إبراهيم، أديسا (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah,al-Jami'ah al-Islamiyah al-'Alamiyah, 2015)
The study is an attempt to explore Abdul Wahhab al-Masiri's exposition on modernity and post- modernity. It is worth mentioning that al-Masiri's views and works on issue related to Western modernity are seen as a new significant in the contemporary intellectual discourse. It is observed that al-Masiri is critical to the Western archetype because, according to him the West has become the most prevalent at present time. The rest of the world which are non-Western, are consciously or unconsciously copying the western model. Believing that the current Western paradigm is based on simplistic, reductionist, monistic and materialistic grounds, al-Masiri has suggested a more comprehensive model as an alternative worldview. The study, therefore, discusses particularly the concept of modernity and post-modernity and their historical developments as an introduction to al-Masiri's views. In fact, modernity and post-modernity have been recently overshadowed by a number of contradictions that made both discourses subject of critique by some Western intellectuals. Hence, al-Masiri focuses on the epistemological foundation of modernity and post-modernity as well as their historical developments throughout centuries to demonstrate the Western model is no longer effective enough to be emulated and to suggest Islam as an alternative to the Western model by emphasizing that Islam has all the adequate elements to solve the problems and challenges faced by humanity. al-Masiri is also critical about the Western materialistic elements, the solid and the fluid that manifest in a comprehensive-secular outlook where human beings are made or looked at as the centre of the universe, and where nature or matter is looked at as subservient to human beings. In fact, it was during the Western Renaissance and the age of discovery that 'humanism' was predominant. As time passes, however, the central point that was once in the hands of human beings has become the prerogative of nature or matter. That is to say materialism has taken control over what was once enjoyed by human beings. Materialism is also taken over by another stage along the way to hierarchy – by post-modernity. In a response to these contradictions, al-Masiri suggests Islamic modernity. In fact, this is considered as a good attempt by al-Masiri to revive ilm al-kalam. However, this study questions al-Masiri's adoption of what he coins “partial secularism” which he regards as an offshoot of Islamic modernity. Hence, the study aims to investigate the theory of Islamization of knowledge as a conceptual framework that represents the basic teachings of Islam. The study sums up with several conclusions about al-Masiri's view vis-à-vis modernity and post-modernity. The study suggests that there should be other extensive studies to investigate the different thoughts proposed by Muslim intellectuals on the issue of modernity and post-modernity, and to characterize those views and thought, in the future.